Stocker & Dehner's pediatric pathology - Stocker, J. Thomas.; Dehner, Louis P., 1940-; Husain, Aliya N. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Revised and updated for its Third Edition, Stocker and Dehner's Pediatric Pathology provides encyclopedic coverage of the diagnosis of pediatric disorders from the neonatal period through adolescence. It covers all major aspects of the pathologic anatomy of childhood disorders ranging from chromosomal syndromes and neoplasms to forensic pathology. Sections are organized by disease classification and by organ system. The book contains more than 1,300 gross and microscopic images, including 1,200 in full color. This edition includes a new chapter on transplantation pathology. Other highlights include significant updates in the areas of pediatric autopsy, imaging techniques, molecular techniques, embryonic and fetal wastage, congenital abnormalities, metabolic disorders, SIDS and forensic pathology, the placenta, and the nervous system"--Provided by publisher.